Investigating the Wettability, Rheological, and Tribological Properties of Ammonium-Based Protic Ionic Liquids as Neat Lubricants for Steel–Steel and Steel–Aluminium Contacts - B. Depu Kumar Patro; P. S. Suvin; Raimondas Kreivaitis; Milda Gumbytė (Lubricants, 2023)
This study aims to evaluate the tribological properties of two protic ionic liquids (PILs) under different tribological conditions as a sustainable alternative for mineral oil-based neat lubricants. The synthesis of PILs in this study uses a relatively simple and less expensive method. The Fourier transform infrared (FTIR) spectroscopy results help validate the synthesised PILs’ formation. Further, their physicochemical and tribological properties were investigated. The PILs as neat lubricants were tested on a ball-on-plate reciprocating tribometer using bearing steel–bearing steel and bearing steel–aluminium alloy friction pairs at 30 °C and 80 °C. The results show that the investigated PILs significantly reduced the coefficient of friction and wear. The dodecylamine-based PILs performed better in friction and wear reduction than the other investigated lubricants. The formation of the adsorption layer on the friction pairs was assumed to be the dominant friction and wear reduction mechanism.